2012
DOI: 10.1007/s10856-012-4616-4
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Raman microscopy and SEM/EDS investigations of the interface between the zirconia core and veneering ceramic: the influence of a liner and regeneration firing

Abstract: The aim of this study was to evaluate the changes in the transition layer at the interface between yttria partial stabilized tetragonal zirconia polycrystalline (Y-TZP) core and veneering feldspathic ceramic (VITA VM(®)9), under different manufacturing methods. Confocal Raman microscopy and energy dispersive X-ray spectroscopy (EDS) analyses were carried out on tapered veneered cross sections of the interface. For some samples, an additional firing of the core was used, as the application of an optional liner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…There are other studies that bring the chemical proportions of the porcelain with and without the presence of C, [62] as done in this study, or even report the obtained values and do not go in further details on the presence of this element [63]. Feldspathic VM9 porcelain, Enamic and Lava Ultimate chemical composition, obtained from XPS analyses, were consistent to previous studies [59,62,64,65] and showed agreement with the atomic proportions obtained in previous works [66][67][68][69].…”
Section: Discussionsupporting
confidence: 91%
“…There are other studies that bring the chemical proportions of the porcelain with and without the presence of C, [62] as done in this study, or even report the obtained values and do not go in further details on the presence of this element [63]. Feldspathic VM9 porcelain, Enamic and Lava Ultimate chemical composition, obtained from XPS analyses, were consistent to previous studies [59,62,64,65] and showed agreement with the atomic proportions obtained in previous works [66][67][68][69].…”
Section: Discussionsupporting
confidence: 91%
“…Studies of microscopic analysis on the zirconia/feldspathic porcelain interface also revealed a mutual diffusion process, with an estimated elemental transition area having a maximum thickness of 2 mm [32]. It was also proposed that the mutual diffusion area tends to increase with the application of the liner [33]. In agreement with previous findings, the line profile analysis of EDS in the present study showed the transition of elements at the bonded interface.…”
Section: Discussionsupporting
confidence: 91%
“…The observation of this transformation for the nonfractured veneered copings can be explained by the diffusion of the veneer into the surface of zirconia during the firing processes, which results in a high stress concentration at the veneer-framework interface. Durand et al 39,40 confirms this suggestion. In the case of nonfractured veneered copings, the temperature gradient factor is excluded.…”
Section: Discussionmentioning
confidence: 77%